Issues of Practices in Matrimonial Partnership and Parenthood - Yatsyna, Olena (Psychological Prospects Journal, 2015)
The article deals with the analysis of the content of various practices of matrimonial partnership and parenthood, the formation and coexistence of which became possible due to the pluralisation of the discourse of the traditional family, marriage and parenthood. Practices are considered as social  constructs,  their  plurality being provided by freedom of discourse choice. The family, marriage, parenthood discourse constructs social meanings, reflecting the way of life, where, along with traditional forms of marriage and family relationships is made possible another beyond- structural and non-linear way of integrity, that enables the individual to form different identities, choosing freely different practices of matrimonial partnership and parenthood. It is mentioned that the tendency to erase the boundaries between opposing entities that is manifested in a different attitude to sexual identity (presented by models of homosexual or lesbian relations practices) is another way to organize the individual's own life. Within the marriage and family relationship discourse pluralisation, men/women can acquire a new identity, each of which implies a certain behaviour in the context of different practices of partnership and parenthood. Modern realities show us the different types of gender identity, their practicing is caused by the individual choice. It is noted that transgendernism is characterized by mobility and fluctuation in relation to pre-existing immutable gender roles and sex. The personality constructs its vital (life) world in accordance with its intentions and changes in an appropriate way. Therefore, the family, marriage, parenthood are flexible discursive constructs where are problematised discursive practices. The  author suggests that there is a semantic differential in vital (life) senses of practice constructions of the past and present as a natural change of generations, values, motivational attitudes (sets), sexuality, intimacy, femininity, masculinity, androgyny, asexuality, parenthood.